The Role of Work Engagement as Moderator of Perceived Stress toward Innovative Work Behavior - Astika Syafitri; Arum Etikariena (Universitas Ahmad Dahlan, 2023)
Previous studies stated that innovative work behavior is negatively affected by perceived stress and positively correlated with work engagement. Work engagement plays an essential role in reducing the effect of perceived stress. This study aims to determine the moderating role of work engagement between perceived stress and innovative work behavior. This research is cross-sectional non-experimental quantitative research. Data were collected among 263 healthcare workers using IWB-9, PSS-10, and UWES-9 as instruments. The data were analyzed with moderation using Hayes’s PROCESS program on SPSS Statistics v22.0.0. This study showed that Work Engagement has no significant role as a moderator on the effect of Perceived Stress on Innovative Work Behavior (t = .14; p = .89 > .05) on healthcare workers. The findings also implied that the negative antecedent variables do not affect innovative work behavior; therefore, the following studies should examine other positive variables on innovative work behavior.